Pore Morphology Tailoring in Polymer‐Derived Ceramics Generated through Photopolymerization‐Assisted Solidification Templating. Issue 6 (3rd April 2019) - Mikl, Gregor; Obmann, Richard; Schörpf, Sebastian; Liska, Robert; Konegger, Thomas
Abstract : A new processing approach combining solidification templating of initially liquid preceramic polymers with a low‐temperature, photoinduced cross‐linking step based on a thiol‐ene click reaction was recently introduced, allowing for the generation of porous polysilazane‐derived ceramics with directionally aligned pore channels. In this work, the focus is set on investigating the roles of the type of structure‐directing solvent, the addition of nucleating agents, and the initial precursor content on the resulting porosity, pore morphology, and properties of ceramics generated through this technique. The variation of the structure‐directing solvent facilitates the generation of various pore channel morphologies, ranging from dendritic to lamellar and columnar structures. The generated materials are evaluated with regard to gas permeability and compressive strength. Depending on the processing parameters, porosity between 40% and 78% is achieved, with median pore opening sizes ranging from 7 to 70 μm. Consequently, a large range of gas permeability (3 · 10 −13 m 2 to 1 · 10 −10 m 2 ) and compressive strength values (0.7 to 51 MPa) are observed. The results show that photopolymerization‐assisted solidification templating of preceramic polymers is indeed a robust technique for a wide parameter range, allowing for the generation of well‐tailored pore structures for various prospective fields of application. Abstract : Polysilazane‐derived ceramics with aligned porosity are generated by solidification templating in combination with "click"‐chemistry‐based photopolymerization. The pore morphology can be controlled by a selection of suitable structure‐directing solvents, resulting in dendritic, lamellar, or columnar pore channels. The approach presented in this paper facilitates the tailoring of porous ceramics toward applications requiring specific permeability and strength characteristics.